From Repatriation to Medium Enterprise: A Narrative Review of OFW Entrepreneurship and Scaling Barriers in the Philippines - Tindugan, Ruben B. (Future Science / FSH-PH Publications, 2025)
This narrative-plus-structured literature review examines how repatriated Overseas Filipino Workers in the Philippines move from necessity entrepreneurship to sustainable medium-scale enterprises and where support systems fall short. Sources from 2019 to 2025 were screened for methodological clarity and local relevance, then synthesized across five lenses: finance and cash discipline; governance and compliance; managerial capability and operating discipline; market access and supply-chain linkages; and technology and digitalization. The synthesis finds that while the ecosystem lowers entry barriers for micro start-ups, the pathway to scale remains thin. Lender legibility is uneven. Formalization and e-documentation requirements slow participation in formal markets. Supervisory depth and operating cadence often stall during the shift from founder-run to professionally managed. Accreditation and purchase-order documentation are pivotal for stable demand and financing unlocks. Basic digital tools shorten cycles and reduce errors when integrated into daily work. An actionable bundle emerges: monthly close within 10 days, a 13-week cash forecast, a compliance calendar and approvals policy, onboarding to e-invoicing and digital payments embedded in accounting and order tracking, a buyer documentation pack with on-time-in-full tracking, and supplier-focused coaching to build lender legibility. Moving from micro to medium scale is most likely when these elements operate together. Policy should test this bundle using longitudinal cohorts and quasi- experimental designs. Future research should track adoption fidelity, heterogeneity by sector and region, and lender responses to improvements in documentation and cash discipline.